Pemberdayaan UMKM melalui Digitalisasi dalam Mendukung Pertumbuhan Ekonomi Desa Ngalian, Kecamatan Wadaslintang, Kabupaten Wonosobo - Sambodo, Herman; Hatma, Muhammad Jabal Qubais; Putri, Dyah Ghaniya; Windari, Sahra; Dewi, Syifa Syahrani; Herdito, Gema Tunas; Meyanie, Ericca Salsabilla (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to improve the capacity of Micro, Small, and Medium Enterprises (MSMEs) through digitalization to support village-based economic growth in Ngalian Village, Wadaslintang District, Wonosobo Regency. The main challenges faced by local MSME actors include limited digital literacy, lack of product branding, and minimal utilization of digital platforms for marketing. The implementation methods included field observations, interviews with MSME actors, digitalization training, and assistance in developing digital promotional media. The programs carried out included creating logos and visual identities, product photography, social media account development, and optimization of business locations on digital map services. The results indicate an increased understanding among MSME actors regarding the importance of digital transformation, improved product presentation quality, and expanded market opportunities through digital platforms. MSME digitalization has proven to be an effective strategy in promoting local economic growth based on village potential and enhancing business competitiveness in the digital era.